Balancing medical education with service in the workplace: a qualitative case study. Issue 2 (16th August 2021) - Fish, Rebecca Mary; Gawne, Suzanne Jane; Machin, Laura
Abstract : Purpose: Finding a balance between the provision of quality individualized care and the ongoing education of junior doctors had been flagged as a concern at a large National Health Service (NHS) teaching hospital in the north of England. In response to this, the organization introduced an intervention designed to improve educational culture by providing support to educators, leaders and clinical staff. Design/methodology/approach: This paper features themed results from eight in-depth interviews with educators, consultants and junior doctors to describe and evaluate the process and impact. Findings: Factors that contributed to a positive educational environment included trainees and educators feeling valued, the presence of supportive leaders and the provision of a safe space for learning. Perceived barriers included time constraints, differing motivation and the generic format of formal education. Participants reflected on how the Wrap Around project helped improve the workplace educational culture and offered suggestions for further improvement including the provision of ongoing feedback to learners about their performance. Originality/value: Research aimed at recognizing and resolving the perceived tensions between the priorities of education and health-care delivery has been flagged as a gap in the literature. The authors argue that developing and enhancing collaborative leadership and educational culture within an organization can reduce these tensions for those working on the front line. Future work should focus on addressing the perceived distinction between the two within services.